Proactive and Data-Driven Decision-Making Using Earned Value Analysis in Infrastructure Projects - Bayram Ateş; Mohammad Azim Eirgash (Buildings)
Timely and informed decision-making is essential for the successful execution of construction projects, where delays and cost overruns frequently pose significant risks. Earned value analysis (EVA) provides a robust, integrated framework that combines scope, schedule, and cost performance to support proactive project control. This study investigates the effectiveness of EVA as a decision-support tool by applying it to two real-life construction case studies. Key performance indicators, including Cost Performance Index (CPI), Schedule Performance Index (SPI), Estimate at Completion (EAC), and Estimate to Complete (ETC), are calculated and analyzed over a specific monitoring period. The analysis revealed a 15.36% cost savings and a 10.42% schedule improvement during the monitored period. By comparing planned and actual performance data, the study demonstrates how EVA enables early detection of deviations, thereby empowering project managers to implement timely corrective actions. The findings highlight EVA’s practical utility in improving project transparency, enhancing cost and schedule control, and supporting strategic decision-making in real-world construction environments.